Pengaruh strategi pengelolaan anggaran, investasi publik, dan manajemen keuangan publik dalam mewujudkan bonus demografis di Jawa Barat - Lugina Handy, Viendy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The province of West Java is projected to see a demographic boost between the years 2015 and 2045. The concept of a demographic bonus refers to a situation in which the working-age population holds a significant majority within a certain population. This phenomenon may provide both advantageous and potentially detrimental implications for the region of West Java. The aim of this study is to present a comprehensive analysis of the impact of independent variables, such as public budget allocation strategies, public investment, and public financial management, on the dependent variable of Economic growth in West Java. The ultimate goal is to harness the demographic bonus in the region. The present study employs a quantitative methodology, using secondary data obtained from many sources. The findings of this research suggest that economic development is influenced by regional financial management techniques, public investment, and local government financial management. This study illustrates the substantial influence of the government in the allocation of budgets, with a focus on directing resources towards appropriate sectors. Additionally, public investment in infrastructure is identified as a key factor in facilitating community mobility. Furthermore, the effective management of finances is deemed critical in endeavors to bolster economic growth within the framework of the demographic bonus.